Docility is not Passiveness: Teaching Learners to Learn in Science Education - Beeler, Dori (Philosophy, theology and the sciences, 2018)
In this article we identify the need for active docility in teaching learners how to learn. Docility is understood not in the quotidian sense, but rather in a virtue ethics tradition where docility is a quality of character described as being both open to learning but also critical of the knowledge being assimilated. In considering the structures of science education, we present case studies from laboratory ethnography that help to illuminate the ways in which docility is crucial not only to learning how to learn, but also to the everyday requirements of the reproducibility of scientific data. In the analysis of the case studies, we highlight three key points: first, the challenges of exemplarity and maintaining pedagogical authority; second, the difficulty of striking the proper 'mean' of docility within different settings; and third, the need for cultivating docility that does not silo instances of learning.